EFFECTIVE SOLUTIONS FOR THERMOELECTRIC HEAT TRANSFORMERS USING HEAT CONVERTERS - A. S. Marchenko; A. B. Sulin (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The present article is based on the examination of the causes of thermodynamic heat loss in thermoelectric heat transformers. It is shown that the external loss in a real system is comparable to the internal loss in thermoelements at the present stage of thermoelectric engineering instrument development. External technical losses are attributed to the irreversibility of processes in system elements. These are determined by their technical resolution and can be lowered by means of specific approaches to design and construction. Methods. Examples of effective technical solutions for thermoelectric units of the "air-to-air" and "air-to-liquid" types, in which external losses are minimised due to the application of heat exchangers based on two-phase thermosyphons of special configuration, are given. For air coolers with a classic all-metal fin design based on the sensitivity analysis method, the dependence of the thermoelectric unit efficiency on the heat exchanger characteristics was calculated. Results. As a result, calculations of the dependence of cooling unit refrigeration capacity on the energy transformation ratio, power transfer coefficient, energy conversion efficiency (ECE) and the relative energetic efficiency of ECE were performed based on the characteristic of the heat exchanger air passage geometry. There is a dependence relationship between the thermoelectric conversion cooling unit refrigeration capacity and transformation ratio within the function of material and thickness of the ribs on the intercostal distance and on the height of the air heat exchanger channel. Conclusion. Examples of the proposed effective thermal circuit technical solutions are based on thermoelectricheat transformers with heat flow direction change and with heat exchangers, which are based on two-phase thermosyphons. Classical solutions of all-metal heat exchangers can also be optimised on the basis of the sensitivity analysis methodology.